Are we ready yet? A qualitative study exploring undergraduate medical students’ readiness for psychiatry placements - Ellen Davies; Scott R. Clark; Adam Montagu; Anna Chur-Hansen (BMC Medical Education)
Abstract Background The purpose of this study was to better understand students’ experiences of readiness for their psychiatry clinical placement and eventual clinical practice in mental health units. Methods Interviews with fourth year undergraduate medical students were conducted and analysed using reflexive thematic analysis. Themes were identified that describe participant experiences of preparation and readiness for placements in mental health units. Results Eight participants provided detailed accounts of experiences prior to medical school, during medical school and during placements in mental health units that influenced their perceptions and attitudes towards people who experience mental illness and mental distress. Themes identified in this study included: Conceptual readiness (and unreadiness), Procedural readiness (and unreadiness) and, Dispositional readiness (and unreadiness). Findings indicate that students do not approach their mental health placements in the same way as they do for other placements. They fear many components of mental health environments, including their own capacity to engage with people without causing further harm. Students had varied attitudes and experiences that shaped their conceptual ideas relating to psychiatry and their procedural readiness to undertaken tasks such as communicating with, and assessment of people experiencing mental distress and mental illnesses. Conclusion Medical students will encounter people who experience mental illness and mental distress regardless of which discipline they choose to specialise. We have an obligation to support students to feel conceptually, procedurally and dispositionally ready to learn and practice when they prepare for clinical placement in mental health units, and indeed for their future practice. Trial registration Not applicable.